2016
DOI: 10.1103/physrevlett.117.230601
|View full text |Cite
|
Sign up to set email alerts
|

Interevent Correlations from Avalanches Hiding Below the Detection Threshold

Abstract: Numerous systems ranging from deformation of materials to earthquakes exhibit bursty dynamics, which consist of a sequence of events with a broad event size distribution. Very often these events are observed to be temporally correlated or clustered, evidenced by power-law distributed waiting times separating two consecutive activity bursts. We show how such inter-event correlations arise simply because of a finite detection threshold, created by the limited sensitivity of the measurement apparatus, or used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 46 publications
(87 reference statements)
7
69
2
Order By: Relevance
“…Ultimately, the question of which mechanism is responsible for the empirical observations of interevent correlations in a given system should be tested in each case, e.g., by employing our scaling predictions as discussed after Eq. (1) of our Letter [1], since various mechanisms including inertial effects or viscoelasticity [11] could also play a role.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Ultimately, the question of which mechanism is responsible for the empirical observations of interevent correlations in a given system should be tested in each case, e.g., by employing our scaling predictions as discussed after Eq. (1) of our Letter [1], since various mechanisms including inertial effects or viscoelasticity [11] could also play a role.…”
mentioning
confidence: 81%
“…Janićević et al Reply: Recently, we proposed a general mechanism leading to power-law distributed waiting times separating avalanches measured in a crackling-noise signal, due to their detection procedure [1]. We demonstrated its applicability for experimental and numerical data on intermittent crack front dynamics.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Petermann et al (2009) compared results for different thresholds in LFPs time series and found that exponent values remain unchanged, suggesting the existence of a truly scale-invariant organization of events. However, a word of caution is still required as recent works have underlined the "perils" associated with thresholding, which in some controlled cases has been shown to generate spurious effects such as effective exponent values and correlations in the timings of consecutive avalanches (Font-Clos et al, 2015;Janićević et al, 2016;Laurson et al, 2009). Further clarifying this issue is key to make solid progress in the empirical analysis of avalanching systems.…”
Section: The Edge Of Activity Propagation: Avalanchesmentioning
confidence: 99%
“…For example, correlations have been observed in stick-slip models with dissipation [76,80], yet they were shown not to be a consequence of event-event triggering but a consequence of slow temporal variations in the Poisson intensity or synchronization [81]. Power-law waiting times can also be artificially constructed by a non-quasistatic driving and a thresholding of the activity [82][83][84], without requiring the involvement of any triggering or aftershock process. Event-event triggering or aftershock sequences and the associated temporal correlations are commonly reproduced by introducing additional temporal scales affecting the propagation of the avalanches, without requiring to break the quasistatic condition.…”
Section: B the Generalized Viscoelastic Dfbmmentioning
confidence: 99%